Development of Biodegradable Nonwoven Mulch Mats from Ijuk Fiber for Sustainable Agriculture - Anggunsuri, Dwi Reisalinda; Titinur, Maydha Tresnaning; Totong, Totong (Universitas Insan Cendekia Mandiri, 2025)
Abstract: Nonwoven agrotextile made from ijuk fiber (Arenga pinnata Merr.) was developed as a biodegradable mulch alternative for sustainable tropical agriculture. This study produced mulch mats using a combination of needle punching and thermal bonding at bonding pressures of 25, 50, and 75 bar. Physical and mechanical properties were evaluated in terms of tensile strength, elongation, basis weight, thickness, water absorption, and air and water permeability. The results showed that 75 bar yielded the highest tensile strength (0.19 kN), optimal elongation (15.92 %), and superior water–air permeability, whereas 25 bar excelled in basis weight (46.07 g/m²), thickness (2.55 mm), and water absorption (334.10 %). Pressure variation significantly (p < 0.05) influenced all parameters, indicating that bonding pressure is a key variable for balancing mechanical strength with agronomic functions—drainage, aeration, and moisture retention. With tunable structural and functional performance, ijuk fiber mulch mats offer an eco‑friendly solution capable of replacing single‑use plastic mulches. Scaling up this product could support sustainable agricultural practices and reduce plastic waste in peatland areas. Keywords: agrotextile, mulch mat, ijuk fiber, nonwoven, sustainable